2016
DOI: 10.1016/j.renene.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic performance assessments of a district heating system with geothermal by using advanced exergy analysis

Abstract: a b s t r a c tThis paper relates to thermodynamic performance assessment of a geothermal district heating system (GDHS) using advanced exergetic analysis to identify the interactions among system components and the potential for improvement. It is introduced four new exergetic parameters, namely the exergetic fuel depletion ratio, the exergetic productivity lack ratio, the exergetic rehabilitation ratio, and the exergetic improvement potential for a GDHS. This analysis and new exergetic parameters are applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 38 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…The results showed that the advanced exergetic analysis was a more meaningful and effective tool than the conventional one for the system performance evaluation. The exergetic efficiencies for the conventional and advanced ones were 25.24% and 26.34%, respectively [30].…”
Section: Introductionmentioning
confidence: 96%
“…The results showed that the advanced exergetic analysis was a more meaningful and effective tool than the conventional one for the system performance evaluation. The exergetic efficiencies for the conventional and advanced ones were 25.24% and 26.34%, respectively [30].…”
Section: Introductionmentioning
confidence: 96%
“…The large scale utilization of locally available heat sources makes District Heating (DH) a rational and efficient domestic heating option. To date, this technology has been coupled successfully to high efficiency Combined Heat and Power (CHP) plants [1,2], energy-intensive industries [3,4] and renewable gen-5 eration plants such as solar [5,6], biomass [7,8] and geothermal systems [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exergy analysis is also conducted to incorporate energy quantity and quality at the same time. Exergy is defined as the maximum potential of work obtainable from a substance or a system while it approaches to the reference environment reversibly (Yamankaradeniz 2016). By conducting exergy analysis, the thermodynamic performance of the novel FW treatment system can be identified from an energy quality perspective.…”
Section: Introductionmentioning
confidence: 99%